Increasing the Ability of Social Aspects in The Daily Activities of Children with Visual Impairments through Parental Assistance - Juhanaini, Juhanaini; Meiyani, Neni Meiyani; Anwar, A Rahim K; Istiqomah, Dina (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Introduction to the active role of parents is one of the keys so that children can have social skills in daily life well and independently for visually impaired children. Children spend a lot of time at home and do activities at home so mentoring from parents is very important, as this potential must be increased. The purpose of the research is to make programs to improve the ability of parents to mentor visually impaired children in social skills, especially in daily living activities in the home environment. The method used qualitative research, collecting data with observations and interviews of teachers and parents further based on the results was designed to program and be tested in the field. The findings are still a lack of restraint and the active role of parents towards the condition of visually impaired children, so parents have difficulty in mentoring at home based on the development of programs to increase the role of parents in mentoring the child. The conclusion of the program is effective to improve the understanding and active role of parents in mentoring children to improve the social skills of visually impaired children in the home environment so that the child's development can be more optimal and independent.